2006
DOI: 10.1109/tmi.2006.870892
|View full text |Cite
|
Sign up to set email alerts
|

Lung motion correction on respiratory gated 3-D PET/CT images

Abstract: Motion is a source of degradation in positron emission tomography (PET)/computed tomography (CT) images. As the PET images represent the sum of information over the whole respiratory cycle, attenuation correction with the help of CT images may lead to false staging or quantification of the radioactive uptake especially in the case of small tumors. We present an approach avoiding these difficulties by respiratory-gating the PET data and correcting it for motion with optical flow algorithms. The resulting datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
146
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 25 publications
2
146
0
1
Order By: Relevance
“…In addition, breathing irregularities can significantly reduce the quantification accuracy of 4D PET images and results in FDG uptake values that lie between the true (stationary) and non-gated values [13,16,36]. Typical respiratory patterns commonly demonstrate irregularities rather than a smooth, sinusoidal curve, and such patterns were encountered in our study in some subjects (Fig.…”
Section: A Salavati Et Al: Partial Volume Effect Correction Vs 4d mentioning
confidence: 66%
See 3 more Smart Citations
“…In addition, breathing irregularities can significantly reduce the quantification accuracy of 4D PET images and results in FDG uptake values that lie between the true (stationary) and non-gated values [13,16,36]. Typical respiratory patterns commonly demonstrate irregularities rather than a smooth, sinusoidal curve, and such patterns were encountered in our study in some subjects (Fig.…”
Section: A Salavati Et Al: Partial Volume Effect Correction Vs 4d mentioning
confidence: 66%
“…Since the morphological parameters may prove essential during radiation therapy, our results should not be extended to PET/CT studies performed for radiation treatment planning where the accuracy of SUV quantification may be less important. Second, it has been demonstrated that phasebased respiratory gating is less effective than amplitudebased gating, especially in patients with irregular respiratory cycles [13]. Despite this knowledge, phase-based methods of gating remain the most widely investigated in cancer research [15], as in the current study.…”
Section: A Salavati Et Al: Partial Volume Effect Correction Vs 4d mentioning
confidence: 76%
See 2 more Smart Citations
“…Correction methodologies involve the use of gated frames that are of low signal-to-noise ratio since each frame contains only part of the counts available in a motion-averaged PET study (4)(5)(6). More advanced correction approaches consist of either accounting for motion in image space (7), where respiration-gated images are deformed to a reference state and summed, or incorporating motion parameters into the iterative image reconstruction process to produce a single motion-compensated PET image (8,9). Within the context of motion compensation, it has been previously shown that the necessary motion parameters may be extracted directly from the PET images (10).…”
mentioning
confidence: 99%